2016
DOI: 10.4070/kcj.2016.46.3.394
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity and Hypertension in Association with Diastolic Dysfunction Could Reduce Exercise Capacity

Abstract: Background and ObjectivesEmpirical evidence is lacking on the cumulative disease burden of obesity and hypertension and its impact on cardiac function and exercise capacity. The purpose of this study was to determine whether the presence of obesity and hypertension together was associated with cardiac dysfunction and exercise capacity.Subjects and MethodsUsing a retrospective study design, medical records were reviewed for echocardiographic and treadmill exercise stress test data. Subjects were grouped accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…When the direct and indirect effect occurred in opposite directions, the mediated % is reported to be 0. www.nature.com/scientificreports/ Similarly, to studies carried out in different socioeconomic contexts, we observed that early age at menarche is associated with higher diastolic blood pressure and triglycerides among young adult women 41 . Some studies have shown an intimate relationship between obesity/overweight, assessed by BMI, with diastolic function [42][43][44] , as well as the association between age at menarche and BMI-mediated diastolic blood pressure 23,45 . The use of more accurate measures of body composition to quantify the accumulation of body fat, contribute better to the prevention and intervention in cardiometabolic problems.…”
Section: Discussionmentioning
confidence: 99%
“…When the direct and indirect effect occurred in opposite directions, the mediated % is reported to be 0. www.nature.com/scientificreports/ Similarly, to studies carried out in different socioeconomic contexts, we observed that early age at menarche is associated with higher diastolic blood pressure and triglycerides among young adult women 41 . Some studies have shown an intimate relationship between obesity/overweight, assessed by BMI, with diastolic function [42][43][44] , as well as the association between age at menarche and BMI-mediated diastolic blood pressure 23,45 . The use of more accurate measures of body composition to quantify the accumulation of body fat, contribute better to the prevention and intervention in cardiometabolic problems.…”
Section: Discussionmentioning
confidence: 99%
“…In our population, we also observed a significant association between definitely abnormal diastolic function (meeting three or more of the cutoff values of the 2016 guidelines) and all the parameters assessing the EC (Table 2). Declines in EC are related to numerous factors, including increasing age, being female, a high body mass index and several medical conditions such as diabetes and hypertension [[7], [8], [9]]. In our study, the multiple regression analysis revealed an independent association between these factors and EC, regardless of whether it was measured in terms of VO 2max , number of METS or cardiopulmonary exercise test duration (Table 3).…”
Section: Discussionmentioning
confidence: 49%
“…The association between diastolic dysfunction and VO 2max has also been confirmed in patients with dyspnoea [28] and heart valve disease [29]. Further, the diagnosis of diastolic dysfunction in individuals with cardiovascular risk factors and/or diabetes predicts the development of heart failure [5,9,30] and this may be of great clinical relevance regarding the need for aggressive management of this condition in such individuals.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There have been contradicting opinions on the role of menopause in development of hypertension. Historically, age, increased BMI, and menopause have been suggested as significant risk factors for hypertension in peri-menopausal women [ 23 , 24 ]. Staessen et al emphasized menopause as an important contributor of hypertension even after adjusting for age and BMI [ 5 ].…”
Section: Discussionmentioning
confidence: 99%